Sickness absence trajectories following labour market participation patterns in Catalonia, 2012-2014. (13th November 2019) - Hernando-Rodriguez, J C; Serra-Saurina, L; Benavides, F G; Ubalde-Lopez, M
Abstract: Background: Working life is characterized by transitions between different employment status which could affect future health status. Previous studies on sickness absence (SA) have focused on risk factors in the workplace; however, there is scarce evidence regarding labour market participation (LMP) patterns. The aim of this study is to examine the association between prior LMP patterns and the course of SA. Methods: Cohort study based on a sample of 11, 968 salaried workers affiliated with the Spanish Social Security system, living in Catalonia, who accumulated more than 15 days on SA at least in one quarter during 2012-2014, from three working life cohorts according to the working life stage in 2002: early (18-25 years), middle (26-35 years) and late (36-45 years). Sequence analysis was used to identify LMP patterns (2002-2011). Latent class growth analysis was applied to identify SA trajectories (2012-2014). Finally, crude and adjusted odds ratios (aOR) were estimated using multinomial logistic regression models. Results: Overall, four SA trajectories were identified: low stable (83%-88% of the workers), decreasing (5%-9%), increasing (5%-11%) and high stable (7%-16%) accumulated days on SA, for men and women. Similarly, seven LMP patterns were obtained: stable employment (63%-81%), increasing employment (5%-22%), delayed employment (7%-8%), decreasing employment (4%-10%), varying employment (13%-14%), steeply decreasing employment (9%), and steeply labour market exit (8%). No significant associations were observed among LMP patterns and SA trajectories, except for young men, where an increasing employment pattern was significantly associated with a lower risk to increase days on SA over time (aOR: 0.21 [95% CI: 0.04-0.96]). Conclusions: A prior 10 years of LMP pattern does not seem to show an effect on the course of SA. A closer working life to the SA course could be considered to assess this relationship. Funding: Grants FIS PI17/00220 and PI14/00057 Key messages: A longitudinally approach is warranted to evaluate the relationship between working life and sickness absence. Extended prior working lives are not related to the course of future sickness absence.